ADSORBENT SYNTHESIS FROM Penaeus monodon CHITOSAN AS COPPER ABSORPTION IN ELECTROPLATING LIQUID WASTE - Arif Setiajaya; Annisaa Siti Zulaicha; Iwan Syahjoko Saputra (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
Chitosan in Penaeus monodon is a chitin compound removed from the acetyl group leaving a polysaccharide amine group and is polycationic through the chitin deoxidation process. The purpose of this study was to identify the potential use of chitosan adsorbent from Penaeus monodon (Chi-ShSW) on decreasing levels of copper (Cu) in electroplating industrial wastewater and to analyze the effect of variations in flow rate using chitosan adsorbents on reducing levels of copper (Cu) in electroplating industrial sewage. Chi-ShSW can be an adsorbent to reduce Cu (II) metal ions in the Metal Coating Industry wastewater. The adsorption test was carried out with a continuous flow system with different debits. The highest reduction in Cu waste in the study occurred at a flow rate of 215 ml/minute with a time of 84 minutes with a Cu content in the Metal Coating Industry wastewater of 1.227 mg/l and a reduction efficiency of 75.86%. The utilization of chitosan from Penaeus monodon was successfully synthesized as an adsorbent for the wastewater treatment of the metal coating industry. It can be concluded that Penaeus monodon can be used as an adsorbent to degrade Cu(II) metal ions contained in electroplating wastewater.